Fractional Hadamard and Fej´er-Hadamard inequalities for exponentially m-convex function - MEHMOOD, Sajid; FARID, Ghulam (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
Fractional integral operators play a vital role in the advancement of mathematical inequalities. The aim of this paper is to present the Hadamard and the Fej´er-Hadamard inequalities for generalized fractional integral operators containing Mittag-Leffler function. Exponentially m-convexity is utilized to establish these inequalities. By fixing parameters involved in the Mittag-Leffler function Hadamard and the Fej´er-Hadamard inequalities for various well known fractional integral operators can be obtained. Mathematics Subject Classification (2010): 26B25, 26A33, 26A51, 33E12.